Tiltų perdangų gelžbetoninės plokštės įrąžos - Notkus, Algirdas J. (Journal of Civil Engineering and Management, 1996)
Forces in reinforced concrete bridge deck slabsA distinct difference between forces, especially bending moments, in slabs of slab-and-beam deck of reinforced concrete bridges, determined by the methods of analysis, applied in the former USSR and France, is pointed out in the article. The essence of calculation of forces in the slab due to bridge loads is presented. Deformations of deck as a spatial structure are resolved into local between beams and spatial characteristics for the whole deck. Local bending slab moments due to local deformations are calculated approximately using diagrams of a continuous and with built-in-end beam. It is shown that forces only due to local deformations are evaluated in the method of the former USSR.A more accurate modelling of deck slab behaviour is obtained by using spatial diagrams composed of plate and beam elements or of spatial diagrams composed of plate and beam elements or of even more accurate shell-type elements. Calculations have been performed by the use of three finite-element method programs Lira, Gifts and Staad3. Decks of various length and width are loaded with combinations of permanent and variable, traffic AK and HK-80 loads. More accurately strain and stress states are modelled in non-linear calculations accounting for non- elastic deformation and cracking of slab concrete as well as cracking of beams.The investigation of results has shown that the method of the former USSR, still applied in Lithuania today, erroneously evaluates slab load-effect resulting in unacceptedly reduced positive bending moments in the larger central deck part. Recommendations to calculate these load-effects are proposed. By simplified two-stage- design methods in use to-day when at the first stage basic load effects Mo and Qoare calculated employing diagrams of simple beam (USSR), or that of slab supported on two sides (France), and in the second stage design loads-effects are determined by multiplication of basic values and coefficients. Recommended values of such coefficients for basic bending moments Mo determined by beam method are shown in Fig. 7a, and those by slab method—in Fig. 7b. Other recommendations for evaluation of shear forces and longitudinal moments are also presented.Article in Lithuanian.First Published Online: 26 Jul 2012